Project Delay Factor Analysis Using Fault Tree Analysis (FTA) Method and Rescheduling with Critical Path Method (CPM) in Ducting Manufacturing Projects at PT. FRA - Putra, Festo Renza Ardhana; Widyaningrum, Dzakiyah (Advance Sustainable Science, Engineering and Technology, 2024)
Ducting manufacturing project at PT. The FRA was planned to be completed in 14 days, but was implemented in 19 days and 5 days late. The method to find the cause of project delays is Fault Tree Analysis (FTA), then analyze rescheduling with the Critical Path Method (CPM). The purpose of this study is to identify factors of work delay, determine new steps for project contractors and reschedule with alternative working hours and labor additions. The results of the analysis using the FTA method obtained the main cause of delay in drawing engineering work of 0.0002592 and obtained 4 new steps for project contractors. The results of rescheduling using the CPM method obtained a percentage increase in productivity with the alternative of adding working for 4 hours with a duration of 25% or 6 days faster than the normal duration of 19 days to 13 days and an additional cost of 91.96%, which is Rp. 21,500,000. While the percentage of productivity increase with alternative labor additions with a duration of 38.75% or 5 days faster than the normal duration of 19 days to 14 days and additional costs of 178.57%, namely Rp. 31,200,000. So it can be concluded by using the FTA method the main cause is drawing engineering work and 4 new steps are obtained and using the CPM method alternative scheduling is obtained to increase overtime work hours more effectively and additional costs are not too large, so that the company does not experience delays for future ducting projects.